ANALISIS MODEL EVALUASI PENDIDIKAN KESESUAIAN (CONGRUENCE MODEL) PERSPEKTIF HADITS - janah, Septa miftakul (Tarbawy : Jurnal Pendidikan Islam, 2022)
The position of hadith is as a second guideline after the Qur'an and the foundation in determining all Islamic educational policies. Each component of Islamic education must be accompanied by arguments or reinforcement from the source of Islamic guidelines so that it can be developed despite the changes of the times and this cannot be ignored. One of the components of education is evaluation. The success of the evaluation of the conformity model (congruence model) has been revealed by many studies, but there has been no research on the basis of the evaluation of this conformity model from an Islamic perspective. Based on the research of the hadith in this article, it is found that the hadith narrated by Bukhari about the call to da'wah to the people of the book is authentic in terms of chain and matan. In this article also found the meaning of the hadith narrated by Bukhari and its implications for the evaluation of education that can be used by educators in the assessment process in education.